Acute Rheumatic Fever Presenting with Transient Complete Heart Block: A Rare Cardiac Manifestation in an Adult Patient - Fakhreddine, Omar; Bachou, Ahmad; Sleiman, Jana; Khoury, Maurice (Archives of Clinical and Medical Case Reports, 2025)
Background: Acute rheumatic fever (ARF) is an autoimmune reaction to Group A β-hemolytic streptococcal infection, primarily affecting the heart, joints, and connective tissues. While conduction abnormalities in ARF are uncommon, complete atrioventricular (AV) block is an exceptionally rare manifestation. Case Presentation: We report a case of a 33-year-old breastfeeding woman who presented with fever, sore throat, and myalgia. While under observation in the emergency department, she experienced a transient episode of syncope, during which telemetry captured a complete AV block with a 12-second ventricular pause. Diagnostic workup confirmed acute rheumatic fever based on the revised Jones criteria. Other causes of conduction abnormalities, including myocarditis, sarcoidosis, and autoimmune disorders, were systematically ruled out. The patient was treated with Amoxicillin-Clavulanate and nonsteroidal anti-inflammatory drugs (NSAIDs), leading to complete resolution of the conduction disturbance. A permanent pacemaker was not required. Conclusion: Transient complete heart block is a rare but significant cardiac manifestation of ARF. Clinicians should consider ARF in young patients presenting with unexplained conduction abnormalities. Early recognition and appropriate management are crucial for preventing longterm complications.